Current issues of ensuring state sovereignty of the Russian Federation - A. G. Masalov (Современная наука и инновации)
The article outlines the main theoretical and methodological approaches to determining the essence of the sovereignty of subjects of public relations, examines the qualitative characteristics of the sovereignty of the Russian state, historically conditioned prerequisites and factors of its formation and achievement of the modern state. It is proved that Russian constitutionalism, implemented in the Constitution of the Russian Federation, state strategies and concepts, laws and other normative documents, creates the political and legal foundations for the formation and strengthening of the sovereignty of the Russian Federation.Based on the analysis of modern threats to the sovereignty of the Russian state, the conclusion is substantiated that the consolidation of society is the main direction of strengthening all components, prerequisites and factors of Russian sovereignty.